The Palgrave Handbook of American Mental Health Policy
XXIII, 687 p. 18 illus., 10 illus. in color.
Keywords: This handbook is the definitive resource for understanding current mental health policy controversies, options, and implementation strategies. It offers a thorough review of major issues in mental health policy to inform the policy-making process, presenting the pros and cons of controversial, significant issues through close analyses of data. Some of the topics covered are the effectiveness of various biomedical and psychosocial interventions, the role of mental illness in violence, and the effectiveness of coercive strategies. The handbook presents cases for conditions in which specialized mental health services are needed and those in which it might be better to deliver mental health treatment in mainstream health and social services settings. It also examines the balance between federal, state, and local authority, and the financing models for delivery of efficient and effective mental health services. It is aimed for an audience of policy-makers, researchers, and informed citizens that can contribute to future policy deliberations. .